Media Manipulation and Psychological War in Ukraine and the Republic of Moldova - Vladislav Saran (CES Working Papers, 2016)
Media manipulation and psychological war in Ukraine and the Republic of Moldova is a battleground of various psychological methods in order to subordinate the masses often under cover of alleged common good. In this regard Russian propaganda machinery is one that works perfectly since the Soviet period. Ukrainian crisis swept the struggle for Ukraine's informational space which has also affected neighboring countries, here referring to Moldova. The conflict between Ukraine and Russia now is more ambiguous because information warfare methods and techniques have become more sophisticated and aim directly to misinformation, informational intoxication and propaganda through the media
Keywords: F50; D83; 330; warfare; television; manipulation; Ukraine; Moldova; social media